Mekanisme Resistensi Isoniazid &Mutasi Gen KatG Ser315Thr (G944C) Mycobacterium tuberculosis Sebagai Penyebab TerseringResistensi Isoniazid - Taufiq Siregar, Mara Imam (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2015)
ABSTRACT Resistance to anti-tuberculosis drugs mainly occurs due to a mutation in the genes of Mycobacterium tuberculosis. Mutations can be induced by inadequate therapeutic levels of drug, mainly due to non-compliance for taking the drug. Therefore, the use of anti-tuberculosis drugs inappropriately and irregularly can lead to mutation in the gene encoding the target of anti-tuberculosis drugs. Inadequate therapeutic levels of drug due to non-compliance of patients taking isoniazid was the most frequent causing mutations inÂ  KatG (Ser315Thr) gene. Therefore, concluded that this mutation was the commonest cause of INH resistance and could be a potential genetic marker for predicting MDR-TB. Â 